2020
DOI: 10.1590/2175-7860202071101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Scleria (Cyperaceae) in Amazonian restinga in Pará state, Brazil

Abstract: This study aims to contribute to the knowledge on the taxonomy of Scleria in sandy coastal plains (restinga) in Pará state, Brazil. Material deposited in the herbaria of Museu Paraense Emílio Goeldi (MG), Embrapa Amazônia Oriental (IAN), and Instituto de Estudos Costeiros da Universidade Federal do Pará (HBRA) were analyzed and species were identified using relevant literature, protologues, and types available online. We recorded nine species of Scleria for restinga in the state: Scleria bracteata, S. gaertner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
1
0
1
Order By: Relevance
“…This is supported by the presence of a ligule of trichomes and hypogynium lobes with an entire apex. While preparing our article on the diversity of Scleria in Amazonian restinga vegetation in the state of Pará, Brazil (Schneider & Gil 2020b), we confirmed that the specimens with the contraligule's membranous appendage and pyramidal paniculate inflorescences, which are particular to this phytogeographic domain, as S. violacea.…”
Section: Scleria Martiisupporting
confidence: 62%
See 1 more Smart Citation
“…This is supported by the presence of a ligule of trichomes and hypogynium lobes with an entire apex. While preparing our article on the diversity of Scleria in Amazonian restinga vegetation in the state of Pará, Brazil (Schneider & Gil 2020b), we confirmed that the specimens with the contraligule's membranous appendage and pyramidal paniculate inflorescences, which are particular to this phytogeographic domain, as S. violacea.…”
Section: Scleria Martiisupporting
confidence: 62%
“…Nevertheless, there are still few studies developed in the Brazilian Amazon region. Some local studies have been developed focusing on the Cyperaceae in the state of Pará, such as: (1) Nunes et al (2016) for the "cangas" of Serra dos Carajás; (2) Silva et al (2021) for the "campos de natureza" in the municipality of Cametá; and (3) Schneider et al (2017), Maciel-Silva et al (2018), and Schneider & Gil (2020b) focusing on Rhynchospora, Eleocharis, and Scleria for the "restingas", respectively. These studies provided taxonomic and nomenclatural novelties, and presented new records for the Flora of Pará, which demonstrates the need for further taxonomic research.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, a família Cyperaceae está presente em todos os domínios fitogeográficos, contendo 646 espécies inventariadas e distribuídas em 30 gêneros, onde 30% são consideradas endêmicas (SCHNEIDER et al, 2020), dentre eles, os gêneros com maior diversidade de espécies são, respectivamente, Rhyncospora, Cyperus, Eleocharis e Scleria (SCHNEIDER; THOMAS et al, 2020;MATZENAUER et al, 2020;NUNES et al, 2020).…”
Section: Sumáriounclassified